Model Pendidikan Karakter Berbasis Keluarga Perspektif Islam di Tengah Pendemi Covid-19 - Fiina Tsamrotun Nafisah; Ashif Az Zafi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
This research raises a problem which is related to the character of children, especially in Indonesia in the midst of the Covid-19 pandemic. It must be realized that all parties, especially parents, play a role in creating a future generation of character or virtuous, religious, and good manners, to uphold civilized Indonesia. The purpose of this study is to determine the basis for the development of character education and character education models in the family in the midst of the Covid-19 pandemic. This research is a literature study and the method used is literature study (library research). The results obtained from this study are that in character education in the midst of the Covid-19 pandemic, attention must be paid to the basics of character development consisting of cognitive development, social development, and moral development. These developments can be instilled in children through character education in the family. In the cultivation of character, of course, must use a model that can direct the child towards the desired character. The model is a family-based character education model of Islamic perspective. In the model, the goal of character education in the family, character education program in the family, character education process in the family, and evaluation of character education in the family.